Genome-wide analysis of the TsBLH gene family reveals TsBLH4 involved the regulation of abiotic stresses by interacting with KNOX6 in Toona sinensis - Shuxin Chen; Yuhan Jia; Yuying Yang; Huan Liu; Huiling Chen; Jun Liu; Hengfu Yin; Renying Zhuo; Xiaojiao Han (Plant Stress)
BLH1-like homeobox (BLH) transcription factors are widely distributed in plants and are a subfamily of the three-amino-acid loop extension (TALE) family. They play pivotal roles in plant growth and development processes and mediate plant responses to abiotic stress. However, recent studies on the function of BLHs have primarily focused on model plants or crops. Here, we identified 21 BLH members in the genome of Toona sinensis. The BLH gene family was divided into five subfamilies, each exhibiting variations in exon-intron distribution and motif composition. TsBLH genes exhibited tissue-specific expression, with all genes responding to salt or osmotic stresses. Notably, TsBLH4 was highly expressed in xylem and leaves and was strongly induced by both salt and osmotic stresses in leaves. Additionally, TsBLH4 is a nuclear protein that physically interacts with TsKNOX6, which is localized in the nucleus and the cytomembrane. The transient expression of TsBLH4 and TsKNOX6 genes in leaves of T. sinensis resulted in increased sensitivity to salt and enhanced tolerance to osmotic stress. These results provide a theoretical basis for the involvement of the BLH gene family in abiotic stress responses in plants.